1978
DOI: 10.1177/014616727800400233
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reprimanding Transgressions on Subsequent Helping Behavior: Two Field Experiments

Abstract: The relationship between reprimanding individuals for naturally occurring transgressions and their later helping behavior was investigated in two experiments. Admonishing individuals for touching art objects in violation of museum rules or feeding "unauthorized" food to animals in a zoo, increased the likelihood that they would subsequently help a confederate pick up dropped items. Individuals were also more helpful after a severe, rather than a mild reprimand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Whether guilt was involved is more difficult to say, however. After the initial studies, subsequent findings questioned the guilt explanation by indicating that transgressions can stimulate altruistic behavior even among uninvolved observers (Cialdini, Darby, & Vincent, 1973; Konecni, 1972; Rawlings, 1968) and even toward recipients other than the victim (Darlington & Macker, 1966; Katzev, Edelsack, Steinmetz, Walker, & Wright, 1978; Rawlings, 1968). Some studies failed to find the effect (Noel, 1973; Silverman, 1967).…”
Section: Reviews Of Empirical Findingsmentioning
confidence: 99%
“…Whether guilt was involved is more difficult to say, however. After the initial studies, subsequent findings questioned the guilt explanation by indicating that transgressions can stimulate altruistic behavior even among uninvolved observers (Cialdini, Darby, & Vincent, 1973; Konecni, 1972; Rawlings, 1968) and even toward recipients other than the victim (Darlington & Macker, 1966; Katzev, Edelsack, Steinmetz, Walker, & Wright, 1978; Rawlings, 1968). Some studies failed to find the effect (Noel, 1973; Silverman, 1967).…”
Section: Reviews Of Empirical Findingsmentioning
confidence: 99%
“…In addition, during the positive experience provided by the experimenter, the subject may have come to believe that the experimenter was unaware of the transgression (McMillan, 1971;McMillan & Austin, 1971) or had chosen to disregard it (Cialdini et al 1973;Regan, 1971). But transgressions that the subject believed were not public have a substantially reduced impact (Katzev, Edelsack, Steinmetz, Walker, & Wright, 1978;Wallace & Sadalla, 1966). To further add to the interpretational ambiguities, in each study a different cognitive or affective component of the positive manipulation was held responsible for the reduced impact of guilt.…”
mentioning
confidence: 99%
“…The importance of the research and the cognitive model for social norm explanations of helping behavior and of social-norm-based behaviors, in general, was discussed.Research has shown that in many circumstances, persons help more and/or more often when a transgression of some kind occurs prior to the opportunity to help than when no such prior event occurs. Often persons who are in some way responsible for the transgression help both the victim (Carlsmith & Gross, 1969) and a third party (e.g., Katzev, Edelsack, Steinmetz, Walker, & Wright, 1978). In addition, witnessing someone else's transgression has been found to increase observers' helping (e.g., Cialdini, Darby, & Vincent, 1973;Rawlings, 1970).Explanations for this phenomenon have emphasized drive-reduction processes.…”
mentioning
confidence: 99%